Dissection of the Functional Mechanism of Human Gut Bacterial Strain AD16 by Secondary Metabolites’ Identification, Network Pharmacology, and Experimental Validation - Wang, Qin; Wang, Yao; Wang, Ya-Jing; Ma, Nan; Zhou, Yu-Jie; Zhuang, He; Zhang, Xing-Hua; Li, Chang; Pei, Yue-Hu; Liu, Shu-Lin (Frontiers in Pharmacology, 2021)
Gut bacteria plays an important role in several metabolic processes, such as appetite and food intake, absorption of nutrients from the gut. It is also of great importance in the maintenance of the health of the host. However, there was still limited knowledge on function mechanism of human gut bacteria itself. Here we report the identification of one anticancer gut bacterial strain AD16, which exhibited potent suppressive effects on a broad range of solid and blood malignancies. The secondary metabolites of the strain were isolated and characterized by a bioactivity-guided isolation strategy. Five new compounds streptonaphthalens A and B (1-2), pestaloficins F and G (3-4), and eudesmanetetraiol A (5), together with nine previously known compounds were isolated from the effective fraction of AD16. Structures of the new compounds were established by 1D and 2D NMR and MS analysis, and the absolute configurations were determined by the CD method. Analysis of network pharmacology suggested that 3, 2 and 13 could be the key components for the anti-NSCLC activity of AD16. In addition, the PI3K-Akt signaling pathway, proteoglycans in cancers could be involved in anti-NSCLC action of AD16.